Propagation of religious doctrines to Muslims: a legal perspective - Abd Aziz, Shamrahayu (LexisNexis, 2010)
The propagation of religious doctrines and beliefs among Muslims is considered a controversial activity in Malaysia. It has far-reaching implications on the social and political environment of the country and is likely to cause conflicts between various religious/racial groups in the country. Furthermore, the propagation may open rooms for Muslims to apostate. Islam does not compel anyone to embrace it but it does not tolerate apostasy, 1 which is incompatible with its sacred nature as a divinely revealed religion that is based on immutable principles. 2 Since apostasy is prohibited in Islam, any move to encourage apostasy, such as the propagation of other religious doctrines and beliefs among Muslims, must be controlled and restricted. State law (or Act of Parliament, in the case of Federal Territories) may restrict the propagation of any religious doctrines or beliefs among persons professing the religion of Islam. This essay seeks to argue that in Malaysia, the Federal Constitution sanctions restrictions to the propagation of any non-Islamic doctrine and belief among persons professing the religion of Islam. In pursuance of this constitutional endorsement, almost all states have a law controlling and regulating the propagation of religions among Muslims. While the Constitutional Commission did not give any obvious reason for the power of the state to control the propagation, it is submitted that the special position of Islam and the compromise between Muslims and non-Muslims in the process to achieve independence are the foundations for such restrictions.